Rapid Assessment of Cost-effectiveness of COVID-19 Vaccine against Severe Illness in Thailand - Phongwutthipong, Phattarin; Nittayasoot, Natthaprang; Suphanchaimat, Rapeepong (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2023)
Though the benefit of COVID-19 vaccine in preventing severe illness is universally accepted, little is known about its benefit relative to its investment in monetary value. This study aimed to assess the cost-effectiveness of the national COVID-19 vaccination campaign compared to a scenario where this had not been introduced. This study used a test-negative matched case-control study design to analyze the occurrence of severe illness. Then, a societal perspective was applied for cost-effectiveness analysis. The cost calculation involved aggregating expenses from both COVID-19 treatment and productivity loss during sickness or premature death. The incremental cost-effectiveness ratio (ICER) was calculated to compare the hypothetical scenario (no vaccination campaign) with the status quo (the vaccination campaign in place). The study found that the three-dose regimen vaccine effectiveness remained over 80% over a year, 0.99 (95% CI 0.96–1.00) in August 2021 to 0.80 (95% CI 0.62–0.89) in June 2022, potentially preventing 71,913 severe illness cases. The ICER analysis showed that preventing one death incurred an extra cost of USD 23,938. Similarly, preventing one intubated case resulted in an additional cost of USD 45,646. Notably, a reduction of vaccine related cost (including administration cost) greatly improved the cost-effectiveness of the campaign. However, a sole reliance on ICER may be insufficient to determine the vaccine campaign’s effectiveness. Therefore, this study suggests further analyses, such as research on willingness to pay threshold and budget impact, to gain a more comprehensive understanding for future policy decision-making.